S2I E-City Shopping Center - LIN, JIE; Malik Ayaz, Muhammad (My University, 2010)
In this thesis classic E-Commerce concept is extended to the concept of an E-City Shopping Center. This concept is rather bound with a city than the whole world. It will provide customers in a specified city with freedom of purchase. It will try to create a virtual city on the internet, in which we will map some of the real city shopping functions. In a real city, the customer can walk on the streets, can do window shopping or buy something, while in a virtual city, the customer can walk on streets with the help of a map, can see different items in a shop, purchase something and can also visit the real shop (by watching its information in the virtual city) to get “Touch and Feel” of the thing. The goal of this thesis report is to analyze and study this new concept, to find different ways and solutions (and to compare them) for its realization, and to implement a prototype, proof of concept, system.
Keywords: Programvaruteknik; Software Engineering